UV/H2O2 Process Under High Intensity UV Irradiation: A Rapid and Effective Method for Methylene Blue Decolorization. Issue 12 (1st July 2013) - Zhang, Qian; Li, Chaolin; Li, Ting
Abstract This study examined the UV/H2O2 decolorization efficiency under high UV photon flux (intensity normalized by photon energy) irradiation; the incident UV was ranging from 3.13 × 10−8 to 3.13 × 10−6 einstein cm−2 s−1. The experimental results showed that complete decolorization of 20 mg L−1 methylene blue (MB) can be achieved within 5 s and 99% decolorization of 1000 mg L−1 MB can be achieved in 180 s under the best condition of high UV intensity UV/H2O2 process. To the best of our knowledge, UV/H2O2 decolorization process in such a short time has not been reported. The electrical energy per order of the process was 16.21 kWh m−3 order−1 and it is relatively economical compared with other advanced oxidation processes. The kinetics of decolorization follows pseudo‐first order. There is a linear relationship between rate constant and UV intensity, which indicates that increasing UV intensity does not cause decline in light utilization efficiency. The experiment related to initial substrate concentration shows decolorization rate of different substrate concentration (20–1000 mg L−1) are closed to each other. Besides, optimal H2O2 concentration, comparative study with low photon flux light, decolorization of other types of dyes and TOC removal were also studied.